PEMBERDAYAAN MASYARAKAT MELALUI DIVERSIFIKASI DAUN KELOR SEBAGAI ALTERNATIF PANGAN SEHAT DI RUMAH SAKIT - Eny Hastuti; Esty Rusida; Azmi Yuniarti; Yustin Ari Prihandini; Guntur Kurniawan (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Seeing that there are still cases of Covid-19 variants of Omicron BA.4 and BA.5, so maintaining immunity during the Covid-19 pandemic is very important. Apart from being required to carry out immunizations, the Ministry of Health uses preparations/compositions of Moringa leaves to increase immunity during the Covid-19 Pandemic. Moringa leaves contain many important nutrients such as vitamins, minerals, amino acids, beta carotene, antioxidants, nutrients, anti-inflammatories, and omega 3 and 6 fatty acids. Diversification of Moringa leaves can also be used to speed up the healing process of diseases in hospital patients. The food served by the hospital is one of the components for the patient's recovery. The training method is carried out by providing counseling and discussion to KWT mothers about the process of diserving processed Moringa leaves. Submission of material is carried out by giving leaflets and direct practice with participants. From the results of this community service, Moringa leaves are being used more and more as alternative snacks in hospitals and in the community, pudding, sticks and Moringa leaf tea